Mechanical and physical behavior of newly developed functionally graded materials and composites of stainless steel 316L with calcium silicate and hydroxyapatite - Oshkour, Azim Ataollahi; Pramanik, Sumit; Mehrali, Mehdi; Yau, Yat Huang; Tarlochan, Faris; Abu Osman, Noor Azuan (Elsevier, 2015)
This study aimed to investigate the structural, physical and mechanical behavior of composites and functionally graded materials (FGMs) made of stainless steel (SS-316L)/hydroxyapatite (HA) and SS-316L/calcium silicate (CS) employing powder metallurgical solid state sintering. The structural analysis using X-ray diffraction showed that the sintering at high temperature led to the reaction between compounds of the SS-316L and HA, while SS-316L and CS remained intact during the sintering process in composites of SS-316L/CS. A dimensional expansion was found in the composites made of 40 and 50 wt% HA. The minimum shrinkage was emerged in 50 wt% CS composite, while the maximum shrinkage was revealed in samples with pure SS-316L, HA and CS. Compressive mechanical properties of SS-316L/HA decreased sharply with increasing of HA content up to 20 wt% and gradually with CS content up to 50 wt% for SS-316L/CS composites. The mechanical properties of the FGM of SS-316L/HA dropped with increase in temperature, while it was improved for the FGM of SS-316L/CS with temperature enhancement. It has been found that the FGMs emerged a better compressive mechanical properties compared to both the composite systems. Therefore, the SS-316L/CS composites and their FGMs have superior compressive mechanical properties to the SS-316L/HA composites and their FGMs and also the newly developed FGMs of SS-316L/CS with improved mechanical and enhanced gradation in physical and structural properties can potentially be utilized in the components with load-bearing application.